2007
DOI: 10.2146/ajhp060558
|View full text |Cite
|
Sign up to set email alerts
|

Strategic approach for improving the medication-use process in health systems: The high-performance pharmacy practice framework

Abstract: The HPP framework characterizes pharmacy performance elements on the basis of feasibility, financial return, and effect on quality and safety. The framework provides pharmacists with a means to establish priorities in improving the medication-use system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…When the physician enters an order for a medication, it is automatically scheduled for a specific time. The times may be completely arbitrary, but this practice allows for efficient automated dispensing, and is based on recommendations from pharmacy and HIT governing bodies (Vermeulen et al, 2007). If the patient prefers to take the medication at a different time (and there is no clinical contraindication for it), the nurse has to attempt to have the medication rescheduled or engage in a workaround.…”
Section: Problems Of Complexity and Technologymentioning
confidence: 99%
“…When the physician enters an order for a medication, it is automatically scheduled for a specific time. The times may be completely arbitrary, but this practice allows for efficient automated dispensing, and is based on recommendations from pharmacy and HIT governing bodies (Vermeulen et al, 2007). If the patient prefers to take the medication at a different time (and there is no clinical contraindication for it), the nurse has to attempt to have the medication rescheduled or engage in a workaround.…”
Section: Problems Of Complexity and Technologymentioning
confidence: 99%
“…Vermeulen et al 8 described a strategic approach for establishing priorities for changes (improvements) in the medication-use process, based on feasibility, the potential for financial return, and the effect on quality and safety. Although this work is not presented as a comprehensive healthsystem pharmacy change model, it does provide useful strategies for establishing priorities, and it should serve as a very useful adjunct to any change model that a health-system pharmacy may adopt.…”
Section: The Nature Of Changementioning
confidence: 99%
“…The elements of this infrastructure can be found in a number of documents, including ASHP's minimum standard for pharmacies in hospitals. 15 Based on the ASHP standard and the other consensus-based sources, 16,17 the essential elements of a pharmacy infrastructure include This list is not all-inclusive. Because of differences among health systems in terms of size, structure, and resources, the organization and prioritization of these elements will vary.…”
Section: Pharmacy Department Infrastructurementioning
confidence: 99%
“…27 Some organizations use the terms "integrated" or "unit-based" pharmacists to describe the model in which pharmacists, in collaboration with technicians, are responsible for all patient needs, including order review and verification, dispensing, and clinical services. 13,16,44 Significant controversy surrounds the patient-centered model versus the specialist model. It has been suggested that more than one model may need to exist within an organization to meet the needs of high-risk populations, such as those in pediatrics, oncology, and transplantation units.…”
Section: Profiles Of Contemporary Pharmacy Practice Modelsmentioning
confidence: 99%